The Idea of Universal Music in Chinese and Western Aesthetics - Motiekaitis, Ramūnas (Acta Orientalia Vilnensia, 2001)
The concepts of Chinese and Western philosophical-aesthetical universal music, or harmony, are discussed in this article. It is also attempted to relate these concepts to existential orientation of civilisations, aesthetical receptions, and forms of artistic creation. The concepts, presented in the article, may be relatively called classical The perceptions of harmony in Confucianism and Han naturphilosophy are compared to Western concepts of “sphere harmony”. On the basis of perceptions of authentic cosmic origin, suggested in the concepts, it is sought to define forms of harmony and its experience. Figure and structure, emerging in the philosophy of Pythagoreans and Plato, testify its extensive-visual nature, which supposes perception of harmony as a concept of abstract principles and harmonious subsistence as subsistence within the idea (of harmony). The key Chinese universal dao testifies the energetic-musical perception of cosmic harmony and respective forms of the harmonious subsistence.